Aggressive end-of-life care in patients with gastrointestinal cancers – a nationwide study from Denmark - Stine Gerhardt; Kirstine Skov Benthien; Suzanne Herling; Marie Villumsen; Peter-Martin Karup (Acta Oncologica)
Background: Knowledge of determinants of aggressive end-of-life care is crucial to organizing effective palliative care for patients with gastrointestinal (GI) cancer.